Expedition into empire
1 online resource (x, 241 pages)
Keywords: "Expeditionary journeys have shaped our world, but the expedition as a cultural form is rarely scrutinized. This book is the first major investigation of the conventions and social practices embedded in team-based exploration. In probing the politics of expedition making, this volume is itself a pioneering journey through the cultures of empire. With contributions from established and emerging scholars, Expedition into Empire plots the rise and transformation of expeditionary journeys from the eighteenth century until the present. Conceived as a series of spotlights on imperial travel and colonial expansion, it roves widely: from the metropolitan centers to the ends of the earth. This collection is both rigorous and accessible, containing lively case studies from writers long immersed in exploration, travel literature, and the dynamics of cross-cultural encounter"--